Factores de riesgo y su incidencia en bronquitis aguda en niños menores de 5 años de la parroquia el Salto Provincia Los Ríos durante el primer semestre 2018 - Sanchez Valero, Katherine De Lourdes (2018)
Introduction.-Bronchitis is a transient inflammation that affects the trachea and the main bronchi, usually associated with respiratory tract infections. These are caused mainly by viruses and usually follow a seasonal pattern with more cases in winter. This research project aims to identify the risk factors that affect acute bronchitis in children under 5 years old, from El Salto parish. the same one that uses a methodology with methods such as: Methodology.-Inductive method This method seeks theoretical sustenance to reach knowledge or demonstration of the truth of the particular facts, proven, makes it possible to reach a general conclusion. Qualitative method We seek to obtain more in-depth information on a particular topic in order to understand what human behavior is in this case acute bronchitis in the case of children under 5 years of age. Quantitative method Also known as quantitative research, it is based on the analysis of numerical data to investigate and verify information and data. Conclusions.-It is concluded that exposure to dust is the main risk factor affecting acute bronchitis in children under 5 years old, from El Salto parish. Environmental contamination, exposure to dust and contact with animals are directly related to the development of acute bronchitis in children under 5 years of age.